2018
DOI: 10.1016/j.acap.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between Parent Proxy Report and Child Self-Report of Pain Intensity and Health-Related Quality of Life After Surgery

Abstract: Although child and parent reports may both contribute important information, parent report is a valid proxy for child self-reported pain intensity and HRQOL after discharge from inpatient pediatric surgery, which may prove important for better understanding pain experiences and intervention needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 26 publications
(38 reference statements)
1
38
0
2
Order By: Relevance
“…For other aspects of mental health, parent-child agreement was shown to be low, e.g., for psychosocial functioning [28], (psycho)somatic symptoms [21,29] and anxiety [30][31][32]. For quality of life, results have been mixed [33][34][35][36], suggesting that agreement might differ depending on contextual factors, e.g., the child's health status.…”
Section: Introductionmentioning
confidence: 99%
“…For other aspects of mental health, parent-child agreement was shown to be low, e.g., for psychosocial functioning [28], (psycho)somatic symptoms [21,29] and anxiety [30][31][32]. For quality of life, results have been mixed [33][34][35][36], suggesting that agreement might differ depending on contextual factors, e.g., the child's health status.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in this context, the parent report can be seen as a valid proxy for child self-reported pain intensity and HRQOL after having undergone pediatric surgery and after discharge. 42 Apart from possible differences in HRQOL assessment between children and their parents, health providers need to be aware of differences in the perception of HRQOL from different family members. Some studies reported that mothers focused more on problems or symptoms than fathers, while others reported no differences.…”
Section: Challenges In Health-related Quality Of Life Assessment In Tmentioning
confidence: 99%
“…Os autores concluĂ­ram que as perceçÔes dos pais e dos enfermeiros sobre a dor dos seus filhos sĂł devem ser consideradas como estimativas da dor experienciada pelas crianças, pois nĂŁo estĂŁo associadas Ă  dor referida pelas crianças. Os outros quatro estudos analisados utilizaram metodologias distintas, mas todos indicaram que a intensidade da dor vivenciada pelas crianças Ă© superior Ă  relatada pelos pais e enfermeiros (Brudvik et al, 2017;Lifland et al, 2017;Kamper et al, 2016;Khin Hla et al, 2014;Rajasagaram, Taylor, Braitberg, Pearsell, & Capp, 2009). Em sĂ­ntese, apesar da escassez dos estudos, verifica-se uma heterogeneidade nas correlaçÔes da avaliação da intensidade da dor entre crianças, pais e enfermeiros.…”
Section: Enquadramentounclassified
“…A tomada de decisĂŁo para o eficaz controlo da dor deve ser coerente com a avaliação percecionada pela criança. Os poucos estudos que analisaram a problemĂĄtica da correlação entre o autorrelato da dor e a avaliação feita por pais e enfermeiros apresentam resultados dĂ­spares, mas com tendĂȘncia consistente da dor relatada pela criança ser normalmente superior Ă  avaliada pelos pais e enfermeiros (Brudvik, Moutte, Baste, & Morken, 2017;Kamper, Dissing, & Hestbaek, 2016;Lifland, Mangione-Smith, Palermo, & Rabbitts, 2017;Zhou, Roberts, & Horgan, 2008). Clarificar a correlação que existe entre o autorrelato da intensidade da dor feita pela criança e a avaliação feita pelos seus pais e enfermeiros permite que na prĂĄtica dos cuidados se tomem decisĂ”es vĂĄlidas no diagnĂłstico da situação e se implementem estratĂ©gias que propiciem um controlo da dor eficaz.…”
Section: Introductionunclassified